Impaired renal clearance among Swedish adolescents born preterm. (8th May 2022) - Skogastierna, Carin; Elfvin, Anders; Hansson, Sverker; Magnusson, Per; Swolin‐Eide, Diana
Abstract: Aim: To determine whether adolescents born before 28 gestational weeks have an increased risk for renal impairment. Methods: Swedish infants, born before 28 gestational weeks in 2001 and 2002, were identified from a local register. A total of 16 children, 12 females and 4 males, were examined at 16–17 years of age with 51 Cr‐EDTA clearance. A comparison group ( n = 26) was used. Results: Most study participants ( n = 13) had normal blood pressure; one individual had hypertension stage 1. All study participants had results within the reference interval for ionised calcium, parathyroid hormone, intact fibroblast growth factor‐23 and for urinary albumin‐to‐creatinine ratio. Four out of 16 participants (25%) had a 51 Cr‐EDTA clearance less than 90 ml/min/1.73 m 2, indicating a reduced kidney function. Measured 51 Cr‐EDTA clearance values were significantly lower in the study group than in the comparison group ( p = 0.0012). Five study participants (31%) were referred for further investigations. Conclusion: Swedish children born before 28 gestational weeks have an increased risk of renal impairment later in life, suggesting that the kidney function in these individuals should be assessed, at least once, during adolescence.